1958
DOI: 10.1002/bscb.19580670705
|View full text |Cite
|
Sign up to set email alerts
|

The Parahydrogen Conversion on Metals

Abstract: La conversion à basse température de l'hydrogène sur l'or diamagnétique fournit, quoique dans une mesure moindre qu'avec l'aluminium paramagnétique, des indications sur les valences libres superficielles postulées dans des calculs sur les chaleurs de chimisorption. L'effet de la pression à 90° K et à 195° K montre que la conversion est d'ordre 0 à basse pression et du premier ordre à pressions élevées. Ceci indique l'existence d'une surface constituée principalement de centres paramagnétiques faiblement adsorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1962
1962
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…That the name E-R mechanism came in use for the reaction between a gas-phase molecule and a chemisorbed molecule may be due to the fact that, after a period of high Interest in the real E-R reaction in the 1940s [8][9][10][11]13], interest waned in the 1950s because it had become clear [39] that the para-ortho H 2 reaction occurs according to the L-H mechanism proposed by Bonhoeffer and Farkas [38]. Interest in the L-R reaction (then called E-R reaction) came up later, first in the 1960s with the CO oxidation reaction [19][20][21] and, after the development of surface science techniques in the 1990s, with studies of molecular beams of light elements reacting with molecules at surfaces [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That the name E-R mechanism came in use for the reaction between a gas-phase molecule and a chemisorbed molecule may be due to the fact that, after a period of high Interest in the real E-R reaction in the 1940s [8][9][10][11]13], interest waned in the 1950s because it had become clear [39] that the para-ortho H 2 reaction occurs according to the L-H mechanism proposed by Bonhoeffer and Farkas [38]. Interest in the L-R reaction (then called E-R reaction) came up later, first in the 1960s with the CO oxidation reaction [19][20][21] and, after the development of surface science techniques in the 1990s, with studies of molecular beams of light elements reacting with molecules at surfaces [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…After World War II interest in the reaction of a chemisorbed H atom with a physisorbed H 2 molecule decreased. In 1958, Eley and coworkers concluded [39] that the para-ortho H 2 reaction occurs according to the Bonhoeffer-Farkas mechanism on all sp metals and on transition metals with the exception of tungsten. On tungsten below 198 K, the para-ortho H 2 reaction occurs according to the Rideal mechanism (Eq.…”
Section: 3 the Real Eley-rideal Mechanismmentioning
confidence: 99%
“…the E–R mechanism could signify reaction of a chemisorbed species either with an incoming molecule from the gas phase or with a physisorbed molecule. By 1958, however, after further papers on the para -H 2 to ortho -H 2 conversion on metals had appeared, Dan concluded that the Bonhoeffer–Farkas mechanism was generally applicable to transition metals at higher temperatures and to sp metals at all temperatures, although the balance of evidence still favoured the Rideal mechanism for tungsten below 198 K (25).…”
Section: The Eley–rideal Mechanismmentioning
confidence: 99%